PENGEMBANGAN BAHAN AJAR PENGETAHUAN LINGKUNGAN BERBASIS WEB UNTUK MENINGKATKAN MOTIVASI MAHASISWA IKIP BUDI UTOMO MALANG - Farizha Irmawati; Ika Oktaviana; Lia Rahayu (UNIVERSITAS PGRI MADIUN, 2016)
The development of rapid information technology makes learners freed in obtaining teaching materials. One of them is a web-based teaching materials. The purpose of the research is to produce a web-based teaching materials on the subjects of Environmental Sciences to enhance student motivation Budi Utomo Malang Teachers' Training College. Development of teaching materials based website using ADDIE models. Development research was conducted from April to December 2015. Based on the results of validation material obtained from the value of 80% and the media expert validation and design to get the value of 93.75% and 83.33%, it means that the teaching materials developed have been fit for use as an ingredient supportingteaching Environmental Science course, but still be revised on the advice and comments from experts as well as students. Web-based teaching materials have been developed and tested on students can create and enhance motivation sebesar 85,75.%.